Riwayat Status Gizi Ibu Hamil, Berat Badan dan Panjang Badan Lahir dengan Kejadian Stunting di Desa “T” Wilayah Kerja PKM “M”, Lebak – Banten. - Syifa Fauziah; Aminah Muin (Akademi Kebidanan La Tansa Mashiro, 2021)
Stunting describes chronic undernutrition during growth and development from early life. This situation is represented by a height-for-age (TB/U) z-score of less than -2 standard deviations (SD) based on WHO growth standards. The purpose of this study was to determine the relationship between the history of nutritional status of pregnant women, birth weight and length with the incidence of stunting in toddlers in the village of